2021
DOI: 10.3389/fphar.2021.750816
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide in Pancreatic Islet Transplantation: A New Therapeutic Alternative to Patients With Severe Type 1 Diabetes Mellitus

Abstract: Pancreatic islet transplantation is a minimally invasive procedure to replace β-cells in a subset of patients with autoimmune type 1 diabetic mellitus, who are extremely sensitive to insulin and lack counter-regulatory measures, and thereby increasing their risk of neuroglycopenia and hypoglycemia unawareness. Thus, pancreatic islet transplantation restores normoglycemia and insulin independence, and prevents long-term surgical complications associated with whole-organ pancreas transplantation. Nonetheless, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…When β cells are stimulated with sodium nitroprusside (SNP, an extracellular NO donor) alone or both sodium nitroprusside and glucose, glucose is still the main factor that induces insulin secretion; NO alone does not induce insulin secretion but only enhances glucose-induced insulin secretion. The mechanism underlying this effect is not clear, but one hypothesis suggests that it may be related to NO-mediated stimulation of transient Ca 2+ release[ 58 ].…”
Section: Neurotransmitters Originating From Both Nerve Endings and No...mentioning
confidence: 99%
“…When β cells are stimulated with sodium nitroprusside (SNP, an extracellular NO donor) alone or both sodium nitroprusside and glucose, glucose is still the main factor that induces insulin secretion; NO alone does not induce insulin secretion but only enhances glucose-induced insulin secretion. The mechanism underlying this effect is not clear, but one hypothesis suggests that it may be related to NO-mediated stimulation of transient Ca 2+ release[ 58 ].…”
Section: Neurotransmitters Originating From Both Nerve Endings and No...mentioning
confidence: 99%
“…Pancreatic transplantation can be a form of treatment in patients with irreversible complications of diabetes, such as diabetic nephropathy [50]. It is now a more and more widely used treatment in adult patients (>18 years old) with T1D of 5 or more years and experiencing unrecognized severe hypoglycaemic episodes [51][52][53][54]. Human islet isolation and purification require a multi-step process to extract the small islet fraction.…”
Section: Pancreas Transplantsmentioning
confidence: 99%
“…Lo et al [357] demonstrated that the hypoxia-induced reduction in insulin secretion could be recovered through the modulation of intermittent oxygen levels between 5 % and 21 % in their culture system. Islets preconditioned in carbon monoxide (CO) have been reported to provide protective effects from the hypoxia-induced cell death after transplantation [359] . Studies revealed that patients who received CO-treated islets had reduced serum levels of CCL23, a chemokine that can recruit immune cells and upregulate several inflammatory cytokines, and increased levels of CXCL12, which can induce angiogenesis and mitigate oxidative stress [359] .…”
Section: Oxygenation Strategiesmentioning
confidence: 99%